Migrasi Magis Subjek Feyre dalam A Court of Throns And Roses Karya Sarah J. Mass - Luhfi, Muhammad; Jannah, Raudhatul; Dwi Jayanti, Nur Fadillah (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes Sarah J. Maas's novel A Court of Thorns and Roses (2015) through the perspective of Jacques Rancière, specifically the concept of distribution of the sensible and subject migration. The focus of the study is directed at the transformation of the character Feyre Archeron who experiences a "magical migration," namely the shift in identity from poor and marginalized humans to the empowered High Fae who have a position in the Prythian social order. This migration is not only physical or biological, but also reflects the political process of emancipation. The subject who was initially "the part that has no part" (the wrong) demands existence within the power structure. The research method uses qualitative descriptive, making the novel ACOTAR as the material object and Rancière's theory as the formal object. Data were obtained through a review of primary texts and secondary sources in the form of articles, journals, and relevant previous studies. The results of the study show that Feyre is positioned as the wrong through social class, gender roles, and species status. Her transformation into the magical world of the Fae reveals a moment of dissensus, when the marginalized subject challenges the partition regime and claims a space of equality. However, this study also uncovers a paradox: post-migration, Feyre continues to face new forms of partition that mark the reproduction of the dominant order in a different form. Furthermore, the novel ACOTAR demonstrates that popular literature functions not only as entertainment but also as a critical medium that represents power relations, identity negotiations, and the politics of equality. This study affirms the potential of popular fantasy literature as a symbolic space for re-reading the dilemma of subject emancipation in contemporary society.